Credit risk and profitability of ASEAN commercial banks: Granger causality test - Tien, Duong Thi Anh (Edelweiss Applied Science and Technology, 2026)
The purpose of this research is to study the profitability and credit risk causality of ASEAN commercial banks. Using data from 118 ASEAN commercial banks from 2002 to 2017, we measure profitability by the ratio of net return to assets (ROA) and net return to equity (ROE). Banking credit risk is measured by the ratio of loan loss provision to assets (LLP). We set up a panel vector autoregression (PVAR) to estimate this relationship. Our results indicate that there is a two-way causal relationship between ASEAN banks’ profitability (measured by ROA) and credit risk. Meanwhile, there is a one-way relationship between profitability by ROE and credit risk, and the opposite direction does not occur. Our results support the "bad management," "skimping," and "moral hazard" hypotheses of Berger and DeYoung [1]. The results of this study provide a basis for informing executive managers to improve the bank's profitability while ensuring safety.